2022
DOI: 10.1177/20587384211073397
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of baicalin against arsenic trioxide-induced acute hepatic injury in mice through JAK2/STAT3 signaling pathway

Abstract: Baicalin (BA) is a kind of flavonoid that is isolated from Scutellaria baicalensis Georgi, which has been verified to have hepatoprotective effects in some diseases. However, the role of BA in acute hepatic injury induced by arsenic trioxide (ATO) remains unclear. The aim of this study was to investigate the protective action of BA on acute hepatic injury induced by ATO and to probe its possible mechanism. Mice were pretreated with BA (50, 100 mg/kg) by gavage. After 7 h, ATO (7.5 mg/kg) was injected intraperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The liver is one of the main target organs of arsenic poisoning [ 6 ]. Previous studies have shown that chronic arsenic exposure can cause liver injury, hepatitis, liver fibrosis, cirrhosis, liver cancer, and other related malignant diseases [ 7 , 8 ]. Population epidemiological investigations and experimental studies have confirmed that arsenic can cause liver damage.…”
Section: Introductionmentioning
confidence: 99%
“…The liver is one of the main target organs of arsenic poisoning [ 6 ]. Previous studies have shown that chronic arsenic exposure can cause liver injury, hepatitis, liver fibrosis, cirrhosis, liver cancer, and other related malignant diseases [ 7 , 8 ]. Population epidemiological investigations and experimental studies have confirmed that arsenic can cause liver damage.…”
Section: Introductionmentioning
confidence: 99%